Tigulixostat Alleviates Hyperuricemic Nephropathy by Promoting M2 Macrophage Polarization - Xue L; Tao Q; Chang H; Yan S; Wang L; Zhao Z; Tu C (Journal of Inflammation Research)
Lina Xue,1,2,* Qianru Tao,1,2,* Haining Chang,1,* Shu Yan,1 Lei Wang,3 Zefang Zhao,4 Chao Tu1 1Department of Internal Medicine, The Third Affiliated Hospital of Soochow University, Changzhou, Jiangsu, People’s Republic of China; 2Department of Nephrology, The Third Affiliated Hospital of Soochow University, Changzhou, Jiangsu, People’s Republic of China; 3Nanjing jinyu medical examination laboratory, Nanjing, Jiangsu, People’s Republic of China; 4Hongyi Honor College, Wuhan University, Wuhan, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chao Tu, Department of Internal Medicine, The Third Affiliated Hospital of Soochow University, 185 Juqian Road, Changzhou, Jiangsu, 213000, People’s Republic of China, Tel +86 15895073069, Email tcmedical21@czfph.comPurpose: Serum uric acid (SUA) is primarily produced through the hydrolysis of purines in the liver, with its excretion largely handled by the kidneys. Urate transporter 1 (URAT1) inhibitors are known to enhance uric acid elimination via the kidneys, but they also increase the risk of kidney stone formation. Currently, xanthine oxidase (XO) inhibitors are the predominant uric-lowering medications on the market.Methods: In this study, we utilized single-cell RNA sequencing, spatial metabolomics, plasma metabolomics, flow cytometry to explore the effects of Tigulixostat on uric acid level and hyperuricemic nephropathy (HN) in Uox-KO mouse model.Results: In this study, we discovered that Tigulixostat (LC350189) more effectively reduced SUA levels and resulted in better renal outcomes compared to allopurinol, without inducing liver injury in urate oxidase knockout (Uox-KO) mice. Mechanistically, we found that Tigulixostat improved HN by promoting M2 macrophage polarization.Conclusion: These findings suggest Tigulixostat as a promising therapeutic option for managing hyperuricemia and related kidney conditions. Keywords: hyperuricemic nephropathy, Uox-KO, tigulixostat, Single-cell RNA sequencing, macrophage